Expression of Human Immunodeficiency Virus Type 1 Gag Modulates Ligand-Induced Downregulation of EGF Receptor - Valiathan, Rajeshwari R. (American Society for Microbiology, 2004)
Many enveloped viruses use the ESCRT proteins of the cellular vacuolar protein sorting pathway for efficient egress from the cell. Recruitment of the ESCRT proteins by human immunodeficiency virus type 1 (HIV-1) Gag is required for HIV-1 particle budding and egress. ESCRT proteins normally function at endosomal membranes, where they facilitate the downregulation of mitogen-activated receptors such as EGF receptor (EGFR) through multivesicular body biogenesis. It is not known whether the Gag-mediated recruitment of ESCRT proteins functionally depletes the pool of these molecules that is available for the downregulation of EGFR. Here we show that the expression of HIV-1 Gag decreases the rate of EGFR downregulation, as assessed by decreases in the rates of (125)I-EGF and EGFR degradation. The effect of Gag was dependent on the presence of the TSG101 binding motif (PTAP) within the Gag C-terminal p6 domain. Cells expressing HIV-1 Gag retained more EGFR in late endosomes. This effect occurred when Gag was expressed alone from a heterologous promoter and when Gag expression was driven by the HIV-1 long terminal repeat within pHXB2ΔBalD25S, a noninfectious lentiviral vector. Gag-expressing cells exhibited higher levels of activated mitogen-activated protein kinase for longer times after EGF addition than did cells that did not express HIV-1 Gag. These results indicate that HIV-1 Gag can impinge upon the functioning of the cellular vacuolar protein sorting pathway and reveal yet another facet of the intricate effects of HIV-1 infection on host cell physiology.